Antibiotic Resistance and Molecular Biological Characteristics of Non-13-Valent-Pneumococcal Conjugate Vaccine Serogroup 15 Streptococcus pneumoniae Isolated From Children in China - Shi, Wei; Du, Qianqian; Yuan, Lin; Gao, Wei; Wang, Qing; Yao, Kaihu (Frontiers in Microbiology, 2022)
Background The isolation rate of serogroup 15 Streptococcus pneumoniae has been increasing since developing countries began administering the 13-valent pneumococcal conjugate vaccine. Methods We detected the antibiotic resistance and molecular characteristics of 126 serogroup 15 S. pneumoniae strains isolated from children in China. Serotypes were determined via the Quellung reaction. Antibiotic resistance was tested using the E-test or disc diffusion method. Sequence types were assigned via multilocus sequence typing. Data were analyzed using WHONET 5.6 software. Results The frequencies of S. pneumoniae serotypes 15A, 15B, 15C, and 15F were 29.37%, 40.48%, 28.57%, and 1.59%, respectively. Continuous-monitoring data from Beijing showed that the annual isolation rates of serogroup 15 S. pneumoniae were 7.64%, 7.17%, 2.58%, 4.35%, 3.85%, 7.41%, and 10.53%, respectively, from 2013 to 2019. All 126 serogroup 15 strains were susceptible to vancomycin and ceftriaxone. The non-susceptibility rate to penicillin was 78.57%. All strains were resistant to erythromycin with high minimum inhibitory concentrations. The multidrug resistance rate was 78.57%. The most common clonal complexes were CC3397, CC6011, CC10088, CC9785 and ST8589. Conclusion Serogroup 15 S. pneumoniae is common among children in China, and these strains should be continuously monitored.